It's no longer the economy, stupid! Issue yield at the 2017 German federal election - Simon T. Franzmann; Heiko Giebler; Thomas Poguntke (West European Politics, 2020)
This article demonstrates that the issue-yield concept is able to predict the electoral strategies of mainstream and challenger parties at the 2017 German federal election. While the electorate of mainstream parties favour valence issues, the Greens and the AfD can gain more by concentrating on socio-cultural positional issues. Relying on a unique survey covering 17 positional issues and 10 valence issues as well as an analysis of Twitter accounts, the article shows that contemporary Germany is characterised by a centrifugal competition on the socio-cultural dimension. At the same time, an asymmetric ideological confrontation persists on the socio-economic dimension, because the Left and the SPD still refer to their traditional welfare issues while the bourgeois parties no longer counter this with a contrasting free-market ideology. Thus, the economy is currently not the decisive issue in German politics. Migration, integration, and other socio-cultural issues are rather driving electoral competition.
doi:10.6084/m9.figshare.10075346.v1
Keywords: 330; party competition; Germany; issue-yield; socio-cultural dimension; valence issues